2022
DOI: 10.1111/exsy.13215
|View full text |Cite
|
Sign up to set email alerts
|

An inception‐ResNet deep learning approach to classify tumours in the ovary as benign and malignant

Abstract: The classification of tumours into benign and malignant continues to date to be a very relevant and significant research topic in the cancer research domain. With the advent of Computer Vision and rapid developments in the fields of deep learning, as well as medical devices and instruments, researchers are therefore utilizing the state‐of‐the‐art deep learning architectures to discover patterns in the medical image data and thereby use this information to detect tumours and classify them as benign or malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…After the region-based training in FaRe-ConvNN, a combination of SVC and Gaussian NB classifiers was used to classify the images, which resulted in impressive precision and recall values [ 17 ]. In the works carried out by Ashwini et al [ 18 , 19 , 20 ], various Deep Learning models were used to segment the CT scanned images and classify them using variants of CNN. In the work [ 18 , 19 ], Otsu’s method was used to segment the tumour and a dice score of 0.82 and Jaccard score of 0.8356 were obtained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the region-based training in FaRe-ConvNN, a combination of SVC and Gaussian NB classifiers was used to classify the images, which resulted in impressive precision and recall values [ 17 ]. In the works carried out by Ashwini et al [ 18 , 19 , 20 ], various Deep Learning models were used to segment the CT scanned images and classify them using variants of CNN. In the work [ 18 , 19 ], Otsu’s method was used to segment the tumour and a dice score of 0.82 and Jaccard score of 0.8356 were obtained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the works carried out by Ashwini et al [18][19][20], the various deep learning models were used to segment the CT scanned images and classified using variants of CNN. In the work [18][19], the Otsu's method was used to segment the tumor and obtained the dice score of 0.82 and Jaccard score of 0.8356.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the works carried out by Ashwini et al [18][19][20], the various deep learning models were used to segment the CT scanned images and classified using variants of CNN. In the work [18][19], the Otsu's method was used to segment the tumor and obtained the dice score of 0.82 and Jaccard score of 0.8356. Further the performance of the segmentation was used cGAN [20], in this study the segmentation and classification of tumors were carried out in the single pipeline and obtained the dice score of 0.91 and the Jaccard score of 0.89.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using DL algorithms like the long short‐term memory model and CNN, they propose a model which will give ***more precise treatment for Ovarian tumours. Ashwini et al (Hegde & Kodipalli, 2022; Kodipalli & Devi, 2021; Kodipalli & Devi, 2023; Kodipalli, Devi, et al, 2022; Kodipalli, Fernandes, et al, 2023; Kodipalli, Guha, et al, 2022; Kodipalli, Gururaj, et al, 2023; Ruchitha et al, 2022), contributed extensively to the detection of PCOS using a questionnaire and found that Fuzzy TOPSIS outperformed the SVM algorithm (Kodipalli & Devi, 2021). Watershed and active contour random walker were used in (Ruchitha et al, 2022) for segmenting the ovarian tumour and it was found that the watershed algorithm outperformed the active contour random walker algorithm.…”
Section: Literature Surveymentioning
confidence: 99%
“…The mental condition of women suffering from ovarian cancer was analysed in Kodipalli & Devi, 2023 and Hegde and Kodipalli (2022)) and it was found that women with ovarian cancer have more mental problems compared to women without ovarian cancer. The novel variant of the CNN model to classify ovarian tumours as benign or malignant was proposed in (Kodipalli, Guha, et al, 2022) and the proposed model outperformed the state‐of‐the‐art architectures of 2014 winning architectures of ILSVRC. The novel single pipeline architecture for segmenting and classifying the tumours was proposed in (Kodipalli, Devi, et al, 2022) which not only outperformed in terms of time but also accuracy.…”
Section: Literature Surveymentioning
confidence: 99%